Does Better Performance Associate With Managing More Unit Trust Fund - R. Santharen, Kaliammal (2007)
This research has carried out to analyze the performance of Malaysian unit trust funds for the long-term periods. The period chosen for this research was from January 1990 to December 2001.The NAV values were obtained from 'The Star' and 'The Sun' newspapers, published on monthly basis. The main objective of this study is to explore further on the unit trust performance and also whether the managing companies that managed more than one fund assures better returns to the investors.The KLCI and KLIBOR rate was used as market benchmark in this research.